Morphological Investigation of Li Thin Film Deposited on LiPON Solid Electrolyte and the Influence of Interlayers on It - Serikkazyyeva, A.; Yegamkulov, M.; Raiymbekov, Y.; Uzakbaiuly, B.; Bakenov, Z.; Mukanova, A. (Karagandy University of the name of academician E.A. Buketov, 2025)
All-solid-state thin-film lithium metal batteries (ASSTFBs) hold great promise for next-generation energy storage due to their long cycle life, stability across a wide temperature range, and low self-discharge, making them ideal for applications in wearable devices, medical implants, and IoT systems. Achieving uniform lithi um (Li) deposition on lithium phosphorus oxynitride (LiPON) solid electrolytes is a critical challenge for ad vancing ASSTFBs. This study evaluates the role of various interlayers in improving film uniformity and ad hesion and compares thermal evaporation (TE) and magnetron sputtering (MS) methods for depositing Li films on LiPON. Initial TE trials revealed discontinuous, droplet-like Li particles with poor interconnection and adhesion on the LiPON surface. To address these issues, metallic interlayers (Sn, Al, Ag, Au, Pt) and metal oxides (ZnO, Al2O3) were explored. Among these, Pt demonstrated the most promising results, forming a lithophilic alloy that improved particle connectivity and interface uniformity. MS produced more consistent Li films compared to TE, attributed to its better-controlled deposition rate and reduced thermal effects. How ever, MS requires precautions due to Li's reactivity and potential system contamination. The findings empha size the importance of interlayer selection and deposition method optimization in achieving dense, uniform Li films. This work contributes to the development of high-performance, reliable microbatteries for advanced energy storage applications. Future studies will focus on refining deposition parameters and evaluating elec trochemical performance to further enhance battery efficiency and stability.
LiPON қатты электролитіне тұндырылған жұқа литий пленкасын жəне оған аралық қабаттардың əсерін морфологиялық зерттеу
Морфологическое исследование тонкой пленки лития, осажденной на твердый электролит LiPON, и влияние промежуточных слоев
Keywords: lithium; LiPON; thin film; solid electrolyte; thermal evaporation; magnetron sputtering; all-solid state lithium metal microbattery